Kajian Atas Kitab Hāsyiah al-Sāwī ‘alā Tafsīr al-Jalālayn: Apresiasi Ulama Terhadap Kitab Tafsīr al-Jalālayn - Imam Zaki Fuad (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2013)
This article has listed 16 sharh (commentary) and hāshiyah (annotation) books on the famous book Tafsīr al-Jalālayn, and four books which obviously become as translations of Tafsīr al-Jalālayn in the Archipelago. This survey also briefly explains such sharh and hāshiya books and classifies them into their own fiqh schools. In fact, Tafsīr al-Jalālayn which is written by two persons of al-Shāfi‘ī school is appreciated by later scholars who are in different school. In the last chapter, the article specifically analyzes the book of Hāshiya al-Sāwī which is written by a scholar of a Mālikī fiqh school, in which this book is one of popular sharh within Nusantara pesantrens dominated by Shāfi‘ī school.